The Stress-activated Mitogen-activated Protein Kinase Signaling Cascade Promotes Exit from Mitosis - Reiser, Vladimír (The American Society for Cell Biology, 2006)
In budding yeast, a signaling network known as the mitotic exit network (MEN) triggers exit from mitosis. We find that hypertonic stress allows MEN mutants to exit from mitosis in a manner dependent on the high osmolarity glycerol (HOG) mitogen-activated protein (MAP) kinase cascade. The HOG pathway drives exit from mitosis in MEN mutants by promoting the activation of the MEN effector, the protein phosphatase Cdc14. Activation of Cdc14 depends on the Cdc14 early anaphase release network, a group of proteins that functions in parallel to the MEN to promote Cdc14 function. Notably, exit from mitosis is promoted by the signaling branch defined by the Sho1 osmosensing system, but not by the Sln1 osmosensor of the HOG pathway. Our results suggest that the stress MAP kinase pathway mobilizes programs to promote completion of the cell cycle and entry into G(1) under unfavorable conditions.